Use of Taxonomy of Privacy to Identify Activities Found in Social Networks' Terms of Use - Rodrigues, Fernando de Assis [UNESP]; Goncalves Sant'Ana, Ricardo Cesar [UNESP] (Ergon-verlag, 2016)
The objective of this paper is to describe, on behalf of social network, elements which allow for identification of possible activity that can present potentially harmful effects to users' privacy, executed by either internal or external agents. To achieve this, the Taxonomy of Privacy was used to establish a way to categorize these possible actions found in terms of use, focusing on current guidelines set about issues related with gathering and storing personal data to increase users' perception about privacy issues. The universe of research was delimited to the study from the three prominent social networks at the time. The results are divided into two parts: the first part tries to identify evidence of activity with potential to be harmful to privacy through a linkage of characteristics from excerpts of the terms of use with concepts found of taxonomy; and the second shows comparisons between classifications made possible by taxonomy and their level of occurrence in terms of use studied. It was concluded that applying an appropriate taxonomy can help with the study of terms of use, enabling a perception of potential harmful activities under those terms. Also, it allows new proposals of applications of this methodology in other contexts.
Keywords: data; use; information; activities; terms of use; personal; users; privacy